Leucine-rich repeats and carboxyl terminus are required for interaction of yeast adenylate cyclase with RAS proteins. - Suzuki, N (1990)
A Saccharomyces cerevisiae gene encoding adenylate cyclase has been analyzed by deletion and insertion mutagenesis to localize regions required for activation by the Sa. cerevisiae RAS2 protein. The NH2-terminal 657 amino acids were found to be dispensable for the activation. However, almost all 2-amino acid insertions in the middle 600 residues comprising leucine-rich repeats and deletions in the COOH-terminal 66 residues completely abolished activation by the RAS2 protein, whereas insertion mutations in the other regions generally had no effect. Chimeric adenylate cyclases were constructed by swapping the upstream and downstream portions surrounding the catalytic domains between the Sa. cerevisiae and Schizosaccharomyces pombe adenylate cyclases and examined for activation by the RAS2 protein. We found that the fusion containing both the NH2-terminal 1600 residues and the COOH-terminal 66 residues of the Sa. cerevisiae cyclase rendered the catalytic domain of the Sc. pombe cyclase, which otherwise did not respond to RAS proteins, activatable by the RAS2 protein. Thus the leucine-rich repeats and the COOH terminus of the Sa. cerevisiae adenylate cyclase appear to be required for interaction with RAS proteins.